TINJAUAN HUKUM ISLAM TERHADAP ISTRI PENCARI NAFKAH KELUARGA SEBAGAI BURUH PABRIK (Studi Kasus di Desa Wonoagung Kec. Kasembon Kabupaten Malang) - Kartikaningsih, Yeni; Marsidi, Marsidi (Mitsaqan Ghalizan, 2024)
This research discusses the review of Islamic law regarding family support for wives who work in factories in Wonoagung Village, Kasembon subdistrict, Malang district. Currently, the trend of people's economic work activities seems to be getting stronger, not only men, but women also get good opportunities to work well in the economic and social fields. Regarding the household and the participation of a wife who works as a laborer in the family economy has a very helpful role in the survival of the family. A wife's participation in work is influenced by educational factors and her diploma. The method in this research uses qualitative research with a descriptive qualitative approach. The results of this research indicate that the role of wives living in Wonoagung Village has a dual role as wife to her husband and as mother to her children. A wife who helps earn a living to meet her family's needs. This is done to help ease the husband's burden in meeting his family's needs. Islamic law does not prohibit a wife from earning a living as long as it does not violate Islamic law and even allows her husband to help earn a living for the family as long as he does not neglect his responsibilities as a housewife, because the household requires the role of the husband as head of the family and the wife as a housewife.